Testing the fidelity of zircon as a provenance indicator in fluvial‐fan successions: An example from the Palaeogene Colton Formation, Central Utah, USA - Davide Carraro; Sean P. Gaynor; Dario Ventra; Alexey Ulyanov; Andrea Moscariello (The Depositional Record)
Abstract The stratigraphic, spatial and temporal variability of detrital zircon age populations in continental sedimentary successions is a critical tool in understanding palaeodrainage networks and how these systems distributed detritus within sedimentary basins. However, multiple factors, such as variations in sediment‐transport processes, the scale of the depositional environment and the architecture of the sedimentary succession are often overlooked in detrital zircon studies. This article presents detrital zircon U–Pb geochronology from the fluvial‐dominated Colton Formation in the western Uinta Basin (Utah, USA) to assess the system's provenance and evolution. Significant differences in zircon age populations between the Colton Formation and the overlying Green River Formation suggest a reorganisation of the source‐to‐sink system during the transition between the two lithostratigraphic units. Notably, detrital zircon age spectra are not homogeneous across the Colton Formation, therefore physical morphometric parameters were used to verify the possible influence of selective bias during sediment transport. These data reveal that a relatively finer‐grained population of Precambrian, and to a less extent Mesozoic, zircon grains were affected by hydraulic sorting during transport, resulting in a greater relative abundance of older zircon grains in the distal reaches of the distributive fluvial system, whose basinward decrease in competence would have increased the relative proportion of finer zircon fractions in sandstones. Furthermore, there are different trends in the distributions of zircon age populations relative to their stratigraphic position, highlighting the complex architecture of the fluvial palaeo‐fan. The spatial and stratigraphic variability of provenance signals in fluvial‐fan successions must be carefully evaluated to improve the reliability of source‐to‐sink models and palaeodrainage reconstructions, as autogenically controlled noise can be generated during the dispersal of detrital zircon in fluvial sedimentary systems.